Syrian refugees arriving in Germany: choice of corridor and individual characteristics of forced migrants - Pries, Ludger; Zulfikar Savci, Berna Safak (Frontiers in Sociology, 2023)
In 2015 and 2016, almost two and a half million forced migrants entered the European Union. Most of them arrived in the European Union from Syria, but there were also forced migrants from Iraq, Afghanistan, and other countries. While many of these migrants used the so-called Balkan route after passing through Turkey, others arrived in Greece via Lebanon or Turkey, and some traveled via North African countries, mainly Egypt and Libya. Why did refugees use such different migration corridors? Was it a matter of economic resources, of education and knowledge, or of family ties and social networks? In this paper, we statistically analyze the migration corridors used by Syrian refugees who arrived in Germany between 2014 and 2016. Using a unique dataset of 3,125 refugees, we identify the main migration corridors used Syrian forced migrants and analyze the sociodemographic and journey-related contextual factors associated with the use of these routes. Use of different escape routes was found to correlate with person-related variables and with journey-related contextual factors. The study contributes the debate on the dynamics of forced migration and onward migration.